Absolute Disney. Love songs [compact disc]. - Thornton, Randy; Thornton, Randy; Williams, Joseph (Vocalist); Dworsky, Sally; Lane, Nathan, 1956-; Sabella, Ernie; Edwards, Kristle; Lansbury, Angela, 1925-2022; Salonga, Lea; Kane, Brad; Wright, Samuel E.; Costa, Mary; et al. (Walt Disney Records, 2019)
The new album features some of the best Disney classic love songs of all time, including favorites such as Can You Feel the Love Tonight? from The Lion King; Kiss the Girl from The Little Mermaid; and many more!